IMPLEMENTASI PERATURAN BUPATI NOMOR 29 TAHUN 2019 TENTANG PENGHAPUSAN DENDA SANKSI ADMINISTRASI PAJAK BUMI DAN BANGUNAN DI KABUPATEN BANYUWANGI - Wartonoadi, Wartonoadi; Rahayu, Sri Rahayu; Imaniar, Dimas Imaniar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
Implementation Regulation Regulation Number 29 Of 2019 Concerning Deletion Of Fine Taxes And Building Administration Taxes In Banyuwangi Distric (Study of Implementation of Regent Regulation Number 29 Year 2019 In Efforts to Increase Community Compliance Paying Taxesat Revenue Agency Office of Banyuwangi) This study aims to determine the application of the Regent's Regulation Number 29 of 2019 concerning the Elimination of Sanctions for the Administration of Land and Building Taxes for Rural and Urban Land in the context of the National Day and Banyuwangi Anniversary for the period 1994 to 2018. The researcher also wants to know the effect of the policy of eliminating sanctions. land and building tax administration in rural and urban areas towards the level of community compliance in paying taxes. This research was conducted at the Regional Revenue Agency Office of Banyuwangi Regency. In collecting data researchers used observation techniques, interviews and accompanied by documentation from the data sources studied. The data that researchers obtain both primary and secondary data are categorized according to the type of data required. Then the data were analyzed using qualitative methods the results of which will be described in a description. The results showed that the application of the policy of eliminating fines for administrative sanctions on land and building tax in rural and urban areas had gone well. An increase in public compliance in paying taxes. This can be seen from the increase in land and building tax revenue in rural and urban areas, especially the United Nations tax receivables compared to the previous year's UN tax receivables